Simultaneous Detection of Escherichia coli O157:H7, Salmonella enteritidis, and Listeria monocytogenes at a Very Low Level Using Simultaneous Enrichment Broth and Multichannel SPR Biosensor. Issue 10 (23rd August 2017) - Zhang, Xiaoguang; Tsuji, Sachiko; Kitaoka, Hayato; Kobayashi, Hiroshi; Tamai, Mitsuru; Honjoh, Ken‐ichi; Miyamoto, Takahisa
Abstract : Abstract: Detection of foodborne pathogens at very low levels is still a challenge. A custom‐built multichannel surface plasmon resonance (SPR) biosensor and simultaneous enrichment broth (SEB) were used to develop a simultaneous detection method for 3 important foodborne pathogens, Escherichia coli O157:H7 (O157:H7), Salmonella enteritidis, and Listeria monocytogenes, at a very low level. These 3 foodborne pathogens at a very low level (14, 6, and 28 CFU/25 g (mL) for O157:H7, S. enteritidis, and L. monocytogenes, respectively) were inoculated in SEB and incubated at 37 ˚C for 24 h. Sample prepared from the simultaneous enrichment culture was analyzed using the multichannel SPR biosensor and sensor chip immobilized with polyclonal antibodies specific to each of the target pathogens. O157:H7, S. enteritidis, and L. monocytogenes in chicken were detected simultaneously at an inoculum dose of 14, 6, and 28 CFU/25 g, respectively. Our method using a custom‐built multichannel SPR biosensor and enrichment in SEB is expected as a rapid and simultaneous detection method for low levels of O157:H7, S. enteritidis, and L. monocytogenes in food. Practical Application: Our method is expected as a rapid and simultaneous detection method for pathogens at very low levels. It has great potential for safety control of food and microbiological detection applications.